Determinants Of Patient Loyalty: A Preliminary Study On Muslim Friendly Hospital In Malaysia - Azman, Nurul Amira Irfa; Abdul Rashid, Nurulizwa; Ismail, Norain; Al-Shami, Samer Ali Hussein (The Mattingley Publishing Co., Inc., 2020)
The purpose of the research is to determine the patient loyalty in the Muslim friendly hospitals using the SERVQUAL model in Malaysia. Hospitals around the world seem to slowly concentrate on their service quality policies. With a growing competition service quality plays a critical part in Malaysian Muslim friendly hospital. Nowadays, patients’ loyalty is one of the very important quality aspects in healthcare sectors. Self-administered questionnaire was used to evaluate the loyalty scale of the patients in which patient loyalty was evaluated on the scale of five aspects such as tangible, empathy, assurance, reliability and responsiveness. The study is based on survey approaches for the preliminary pilot test of 100 respondents collected in selected Muslim friendly hospital in Malaysia. Data were analyzed through descriptive statistics and reliability analyzes using SPSS software. The research findings indicate that all aspects of the SERVQUAL model is strongly related to patient loyalty. Therefore, all the service quality dimension is important to increase customer satisfaction and loyalty. The study enlightens the managerial implications and future directions.